(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to describe and analyse the effectiveness of implementing simple vocational sewing skills learning for mildly mentally disabled students in Grade VII at SLB Benpasi Kefamenanu. The study uses a descriptive qualitative approach with the Classroom Action Research (CAR) method, which was carried out in two cycles. The research subjects consisted of four students with mild intellectual disabilities. Data collection was carried out through observation, interviews, and documentation, while learning activities were implemented through demonstration, repeated practice (drill), and intensive individual assistance. The learning material focused on simple sewing skills, such as making straight stitches and producing small handicraft products. The results showed a significant improvement from cycle I to cycle II, both in terms of fine motor skills and the level of independence of the students. The students were increasingly able to follow instructions well, showed more consistent neatness in their sewing, and completed tasks more independently and on time. These findings are supported by the teachers’ adaptive approach to students’ needs and the availability of adequate learning facilities. Thus, simple sewing vocational learning has proven to be effective in increasing the independence and self-confidence of students with mild intellectual disabilities as a life skill.